DIKOTOMI ILMU PERSPEKTIF IMAM GHAZALI DAN PENGARUHNYA TERHDAP KEBIJAKAN PENDIDIKAN DI INDONESIA - Agus Salim (Institut Kariman Wirayudha Sumenep, 2022)
This study discusses the scientific dichotomy of Imam Ghazali and its influence on education policies in Indonesia. In Indonesia, there are two formal breeding institutions, namely religious education under the Ministry of Religion and general education under the Ministry of Culture, Research, and Technology of the Republic of Indonesia. When there are scientific dichotomies and different academic degrees, this will affect the public confidence in the ability of religious college graduates, this of course will not be in accordance with the goals of education in Indonesia which is just and equalizes religious education and general education. To show whether or not there is a dichotomy of science by Imam Ghazali, this research is carried out on Imam Ghozali's statements about the dichotomy of science, either in his work or in quotes from other people's works about Imam Ghazali. This research method uses Library Research, where the data presented is based on the related literature of the literaturE of Imam Ghazali's thoughts on science. The findings of this study stated that Imam Ghazali did not dichotomy of science, Imam Ghazali only classified which science was the first to be studied. The classification of knowledge carried out by Ghazali according to the needs and benefits of science for the students’ knowledge and al-Ghazali's thoughts did not have a significant influence on education policy in Indonesia.